From Bali to Copenhagen: Indonesia's Position and Role in International Negotiation to Establish a Post-Kyoto Protocol Agreement on Climate Change - Hadi, Syamsul (Indonesian Journal of International Law, 2011)
In the light of upcoming end of the Kyoto Protocol in 2012, international society is in the urgent need to arrange a new international agreement to cope more with the issue that has been threatening both today and the future generation. In this context, Indonesia has attempted to contribute a positive role to seek international consensus on the climate change negotiations, including by becoming the host of Un Conference on Climate Change in Bali (2007), whoch resulted in the Bali Roadmap and Bali Action Plan, both of which has become important stepping stone for the Post-Kyoto Protocol international regime. However, the Copenhagen Conference (2009), which was designed to finish the Post-Kyoto Protocol Agreement had notably failed to provide such international consensus, due to the various different views, interests and persepctives amongst developed and developing countries that caused to failure to reach a new binding agreement on the issue of climate change.